Whistleblowing as a countermeasure strategy against food crime. Issue 12 (4th December 2017) - Soon, Jan Mei; Manning, Louise
Abstract : Purpose: The purpose of this paper is to undertake a two-phase desktop review of literature sources in order to conceptualise, frame, and critique existing whistleblowing models and strategies and consider how whistleblowing strategies form part of an effective food crime management system (FCMS) especially for small and medium sized organisations. Design/methodology/approach: Existing literature from academic sources, financial, healthcare, food industries has been reviewed and critiqued in order to construct a conceptual framework that can inform future empirical research. Findings: Whistleblowing strategies can form an effective part of a FCMS. Appropriate regulatory protection of those who whistleblow is crucial to not only safeguard individuals but also to mitigate food crime and protect consumers from loss and potential harm. Barriers to whistleblowing exist and if these are not addressed then individuals will be reluctant to report food crime. Further empirical research is required to assess the influence of these and other factors identified in this research and how they can be overcome. Originality/value: The framework will provide food industry practitioners with guidance on the effective application of whistleblowing strategies within a FCMS.